The Role Of Journal Writing In Teaching Women’s History - Denkler, Ann (Teaching History: A Journal of Methods, 2007)
As part of a new General Education Core Curriculum at Shenandoah University, the history department took advantage of the opportunity to propose innovative, freshman-level seminar classes with low enrollments. Recently our university had also established a Women’s Studies Program geared toward undergraduate minors, so I proposed to teach a course on women’s history through the General Education core to expose newer students to this subject. After three semesters teaching this course, I discovered that a journal-writing requirement is an ideal pedagogical tool for acclimating new students to college-level work, a vital method for exploring women’s history and gender studies, and a promising way to gain direct and evaluative feedback from my classes. By creating and sustaining a critical and reactive journal throughout the semester, students can construct a space where they can learn how to "test the waters" academically: They can create sophisticated and informed arguments and ruminate on the role of gender in their own lives as well as in history. The private space of the journal can be an ideal site in which to begin critical exploration-the type that will serve them well throughout their college years.